Neonatal Hypogycemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The definition of neonatal hypoglycemia has been surveyed at the Department of Child Health, University of Newcastle upon Tyne by reference to 36 textbooks of pediatrics and answers to questionnaires from 178 pediatricians in charge of nurseries with 4 or more intensive care cots.